Influence of physical education learning models on flexibility recovery and functional mobility in martial arts - Fahmy Fachrezzy; Uzizatun Maslikah; Hernawan; Made Bang Redy Utama; Muhammad Gilang Ramadhan; Sri Indah Ihsani; Ayu Purnama Wenly; Saipulloh Ibrahim (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: Flexibility and functional mobility are two important parts of Taekwondo performance. It is thought that new ways of teaching will help athletes recover faster and move better. The purpose of this study was to determine how a Sports Education-based learning model combined with active recovery affected the recovery of flexibility and functional mobility in Taekwondo athletes. Methods: This study was a quasi-experimental study using a pre-test and post-test control group design. Twenty-eight Taekwondo athletes (aged 16 to 20) were divided into two groups. The experimental group using a sports education model with active recovery, and the control group using regular training. The intervention lasted six weeks. The sit-and-reach test and the shoulder-wrist test were used to measure flexibility during the acute and chronic phases. Functional movement screening (FMS) and the multidirectional kick height test were used to assess functional mobility. Results: Multivariate analysis of variance (MANOVA) showed that there were big differences between the groups (p<0.05). The experimental group showed faster recovery of flexibility after exercise, bigger improvements in FMS scores, especially in the active straight leg raise and rotary stability components, and big increases in kicking height and accuracy. Conclusion: The sport education model with active recovery speeds up the recovery of flexibility and improves the functional mobility of Taekwondo athletes. This makes it a good suggestion for developing training programs.